2020
DOI: 10.3390/polym12112463
|View full text |Cite
|
Sign up to set email alerts
|

Erratum: Development of Poly(l-Lactic Acid)-Based Bending Actuators. Polymers 2020, 12, 1187

Abstract: The authors wish to make a change to their published paper [...]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 1 publication
1
1
0
Order By: Relevance
“…Correia et al described bending actuators based on PLA and 1-ethylmethylimidazolium bis(trifluoromethylsulfonyl)imide ([Emim][TFSI]) IL. 22 These results reinforce the idea that PLA may indeed be suitable for the development of environmentally friendly and sustainable devices with high ionic conductivity and good mechanical properties for energy conversion and storage. In this work, two types of imidazolium-based ILs containing either hexafluorophosphate ([PF 6 ] − ) or tetrafluoroborate ([BF 4 ] − ) anions were incorporated into the PLA matrix, and the resulting blended membranes were evaluated concerning their potential use in PEMFCs.…”
Section: Introductionsupporting
confidence: 67%
See 1 more Smart Citation
“…Correia et al described bending actuators based on PLA and 1-ethylmethylimidazolium bis(trifluoromethylsulfonyl)imide ([Emim][TFSI]) IL. 22 These results reinforce the idea that PLA may indeed be suitable for the development of environmentally friendly and sustainable devices with high ionic conductivity and good mechanical properties for energy conversion and storage. In this work, two types of imidazolium-based ILs containing either hexafluorophosphate ([PF 6 ] − ) or tetrafluoroborate ([BF 4 ] − ) anions were incorporated into the PLA matrix, and the resulting blended membranes were evaluated concerning their potential use in PEMFCs.…”
Section: Introductionsupporting
confidence: 67%
“…This class of ILs has been extensively studied in the last decade since they can interact with various chemical species as they offer hydrophobic or hydrophilic regions and a high directional polarizability. , Therefore, [C n C 1 im] + -based ILs are versatile building blocks for the design of molecules with appropriate physical and chemical properties. Imidazolium-based ILs have been evaluated as potential plasticizers and/or lubricants for PLA. Osada et al reported a lithium metal polymer battery working with a polymer electrolyte based on PLA and N -butyl- N -methylpyrrolidinium bis­(trifluoromethane-sulfonyl) imide (Pyr14TFSI), exhibiting remarkably low-charge-transfer resistance and high-temperature stability. Correia et al described bending actuators based on PLA and 1-ethylmethylimidazolium bis­(trifluoromethylsulfonyl)­imide ([Emim]­[TFSI]) IL . These results reinforce the idea that PLA may indeed be suitable for the development of environmentally friendly and sustainable devices with high ionic conductivity and good mechanical properties for energy conversion and storage.…”
Section: Introductionmentioning
confidence: 84%